Immunosuppressive Role of Myeloid-Derived Suppressor Cells and Therapeutic Targeting in Lung Cancer - Jie Ma; Huaxi Xu; Shengjun Wang (Journal of Immunology Research)
Lung cancer is the leading cause of cancer death worldwide due to its late diagnosis and poor outcome. Immunotherapy is becoming more and more encouraging and promising in lung cancer therapy. Myeloid-derived suppressor cells (MDSCs) are the main tumor suppressor factors, and the treatment strategy of targeting MDSCs is gradually emerging. In this review, we summarize what is currently known about the role of MDSCs in lung cancer. In view of the emerging importance of MDSCs in lung cancer, the treatment of targeting MDSCs will be useful to the control of the development and progression of lung cancer. However, the occurrence, metastasis, and survival of cancer is the result of multiple factors and multiple mechanisms, so combined treatments using different strategies will become the major therapy method for lung cancer in the future.